2003
DOI: 10.1099/vir.0.19443-0
|View full text |Cite
|
Sign up to set email alerts
|

Murine pneumotropic virus VP1 virus-like particles (VLPs) bind to several cell types independent of sialic acid residues and do not serologically cross react with murine polyomavirus VP1 VLPs

Abstract: The ability of murine pneumotropic virus (MPtV) major capsid protein VP1 to form virus-like particles (VLPs) was examined. MPtV-VLPs obtained were used to estimate the potential of MPtV to attach to different cells and to assess some characteristics of the MPtV cell receptor. Furthermore, to evaluate if MPtV-VLPs could potentially complement murine polyomavirus (MPyV) VP1 VLPs (MPyV-VLPs) as vectors for prime-boost gene therapy, the capability of MPtV-VLPs to serologically cross react with MPyV-VLPs and to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Neither preimmune nor immune sera specific to influenza virus or SHIV VLPs blocked the HI activity of SHIV VLPs (data not shown). We also observed that this HI activity was not diminished by treatment of VLPs with neuraminidase, indicating that the inhibition is not mediated via interaction of neuraminic acid on VLPs with the HA of influenza virus, consistent with a recent study showing that cell binding properties of murine pneumotropic virus VLPs obtained in an rBV system were neuraminidase resistant (45). However, it was found by electron microscopy that inactive influenza virus is able to form aggregates with SHIV VLPs.…”
Section: Discussionsupporting
confidence: 71%
“…Neither preimmune nor immune sera specific to influenza virus or SHIV VLPs blocked the HI activity of SHIV VLPs (data not shown). We also observed that this HI activity was not diminished by treatment of VLPs with neuraminidase, indicating that the inhibition is not mediated via interaction of neuraminic acid on VLPs with the HA of influenza virus, consistent with a recent study showing that cell binding properties of murine pneumotropic virus VLPs obtained in an rBV system were neuraminidase resistant (45). However, it was found by electron microscopy that inactive influenza virus is able to form aggregates with SHIV VLPs.…”
Section: Discussionsupporting
confidence: 71%
“…The biochemical and cell biological behavior of the Vp3-less Vp1 mutant particles and the Vp1-only particle gives us strong reason to believe that they have structural features similar to those of the SV40 virion. Although we have not characterized these particles structurally by electron microscopy, all previously tested Vp1s from the polyomavirus family, expressed in either bacteria or insect cells (16,22,28,36,45,47,59), have been found to spontaneously form pseudocapsids with sizes (45 to 50 nm in diameter) and shapes similar to those of wild-type virions.…”
Section: Discussionmentioning
confidence: 99%
“…VP2PyVLPs and Her2 PyVLPs were produced in Sf9 cells infected with recombinant baculoviruses and purified by a CsCl gradient (12). MPyV-VP1 VLPs were produced as described (12).…”
Section: Expression and Purification Of Virus-like Particlesmentioning
confidence: 99%